PREFERENSI WARGA KOTA MATARAM TENTANG DAGING PREMIUM - Hermansyah, Hermansyah; Thei, Ruth Stella Petrunela; Dahlanuddin, Dahlanuddin (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
This study aims to examine the preferences of residents of Mataram City, West Nusa Tenggara Province, in choosing and consuming premium beef. Premium meat has recently been produced from cattle on Sumbawa Island and also from cattle developed on Lombok Island in recent years. This study used a survey approach. Interviews were conducted with 86 small-medium income residents of Mataram with an income range of Rp 5 million - Rp 30 million per month. Respondents consisted of housewives and several men. Premium meat consumption in this study was in the form of beef purchased in a special place in fresh or processed form or in the form of premium meat enjoyed in restaurants or cafes. The results showed that the preference of Mataram City residents towards premium meat was relatively good as reflected in the recognition of residents that premium meat is classified as tender, more juice and soft. The frequency and intensity of premium meat consumption by residents of Mataram City, especially in restaurants and cafes, is still relatively limited. More than half (55.81 percent) of Mataram residents enjoy premium meat 1-5 times per month and as many as 23 percent of Mataram residents rarely enjoy premium meat. The rest of the premium meat enjoys quite intensely.